Cyber Security Paradox in MSMEs: Imbalance of Awareness and Implementation in the Digital Era - Haryanto Haryanto (SAINTIS Publishing, 2025)
Cybersecurity is vital in ensuring the sustainability of micro, small, and medium enterprises (MSMEs) in today’s digital landscape. While awareness of cybersecurity threats is rising, implementing effective mitigation measures among MSMEs remains relatively low. This study seeks to analyze the discrepancy between awareness and actual implementation of cybersecurity practices in MSMEs and investigate how management accounting approaches can help address these challenges. This study reviews pertinent academic literature and industry reports using narrative review and conceptual analysis methods. The findings reveal that the primary obstacles to implementing cybersecurity within MSMEs include limited financial resources, a shortage of information technology experts, and a low understanding of the long-term benefits of investing in digital security. To navigate these challenges, management accounting techniques such as cost-benefit analysis, cost control, and risk assessment can assist MSMEs in allocating their resources more efficiently to bolster cybersecurity. This research enhances the existing literature by bridging the fields of cybersecurity and management accounting and offering policy recommendations to improve MSMEs' digital readiness. Further research is necessary to empirically validate the proposed model and investigate the impact of regulation on enhancing cybersecurity in the MSME sector.